Effect of phosphorus fertilizer on the germination and nodulation of soybeans - Vernetti, Francisco de Jesus; Araújo, Solon Cordeiro de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this research was to study the influence of some phosphorus fertilizers on the germination and nodulation of soybeans. A review of literature has indicated that, in general, the germination of soybean seeds is greatly reduced in the presence of fertilizers. Six phosphorus carriers (superphosphate, hyperphosphate, basic slag, bone meal and "fosforita de Olinda" - rock phosphate) were applied close to or in contact with the seed. Soybean varieties used were Hill and Majos. Seeded in wood boxes, filled with sterilized soil, and kept under greenhouse conditions. The conclusions derived from this experiment and within the limits of the study are as follows: (1) The phosphorus fertilizers produced no harmful effects such as, reduced nodulation, or seed injury; (2) Seed size had no effect on the initial development of the seedlings exposed to direct contact with the phosphorus fertilizers or separated from them by a thin layer of soil.